The profile of patients presenting with ST Elevation Myocardial infarction (STEMI) to a regional emergency department in Gauteng, South Africa - Kannai, Jerisha (University of the Witwatersrand, Johannesburg, 2023)
Reasons for the research: Cardiovascular disease creates a significant health and socio-economic burden and accounts for 17 million deaths worldwide which equates to 31% of global deaths. (1) In addition, premature deaths from cardiovascular disease in the working population are predicted to increase by 41% by 2030. (2) STEMI is a global concern, with growing morbidity and mortality. (3, 4, 5, 6, 7) The continual increase in STEMI cases will burden our society and the economy. (3) There are few studies in South Africa (SA) on the STEMI population. Further baseline data on our population are required to inform efforts to improve our health system, patient care and to work towards international best practice. Aims: a. To describe the demographic characteristics of patients presenting with STEMI. b. To describe the clinical presentation (symptoms, signs, risk factors, time to treatment) of patients presenting with STEMI in a regional public hospital in Gauteng. c. To determine if age, gender, race, time of presentation and level of prehospital care is associated with adverse outcomes or the need for additional interventions. d. To compare outcomes of patients (admission to general ward / Cardiac Care Unit (CCU) / Intensive Care Unit (ICU) / death). Methods: This was a retrospective observational transverse / cross sectional registry study. Data was collected from a STEMI register maintained at the Emergency Department (ED) of Tambo Memorial Hospital (TMH) from June 2018 until 31 July 2020. Major results: In our study 68% of patients were male. The most common ages at presentation ranged from 40 - 69 years old, with a mean age of 54.4 years. The commonest risk factors included: being a smoker (77%), history of ischemic heart disease (71%), hypertension (55%). The highest prevalence - occurred in the Caucasian race group. Our population group was predominantly transported by private means (52%). Only 10.11% of patients scored red on triage and 30.34% scored orange. The mean duration of symptoms was less than 12 hours. The mean time: from door-to-ECG was 38.5 minutes, door- to- doctor’s assessment was 31,4 minutes, door- to-adjuncts was 53,9minutes and door-to-needle was 101.9 minutes. The majority of patients were transferred out of the ED to cardiology (46.87%) and the general ward (40.62%). Conclusion statement: Within the public sector, SA does not have sufficient data on the STEMI population. The aim of this study was to shed light on the population at TMH. It is crucial to treat STEMI patients speedily and effectively. The findings of this study suggest that patients presenting with STEMI at TMH are similar to patients in other studies, but the time to treatment is longer than the recommended target times. These findings suggest room for improvement in the management of STEMI at TMH. Due to a small sample size, we did not have significant results when analyzing the population group requiring special interventions.
A research report submitted in partial fulfillment for the degree of Master of Medicine in Emergency Medicine, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Cardiovascular disease; ST Elevation Myocardial infarction (STEMI); Cardiac Care Unit (CCU); Intensive Care Unit (ICU); Emergency Department (ED) of Tambo Memorial Hospital (TMH); Ischemic heart disease; Hypertension; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education